Validation of the type 1 diabetes distress scale (T1-DDS) in a large Danish cohort: Content validation and psychometric properties - L.E. Joensen; P. Lindgreen; K. Olesen; M. Nygaard; D. Hessler; H.U. Andersen; J.O. Christensen; U.L. Kielgast; K. Nørgaard; U. Pedersen-Bjergaard; I. Willaing (Heliyon, 2023)
Aim: To validate the Type 1 Diabetes Distress Scale (T1-DDS) in a large sample of adults with Type 1 diabetes (T1D) from diabetes clinics in Denmark. Methods: Altogether 40 adults with T1D were interviewed to explore the content of T1-DDS in a Danish setting and to validate the translation of the T1-DDS into Danish. Subsequently, a survey including T1-DDS, the Problem Areas In Diabetes scale (PAID-20), fear of hypoglycemia, social support, and diabetes duration was answered by 2201 people with T1D. Other person characteristics were collected from the National Patient Register. HbA1c was obtained from the Clinical Laboratory Information System. Data distribution, internal consistency, convergent and construct validity, factor structure, three weeks retest, and cut-points were explored. Results: Interview data supported the relevance of all T1-DDS items for the assessment of diabetes distress among adults with T1D. The T1-DDS showed good content and acceptable construct validity, and the ability to detect high diabetes distress levels. A high correlation between T1-DDS and PAID-20 (rho = 0.91) was found. The retest scores showed a good reliability (all rho ≥0.68) with the highest variability in the Friends/Family Distress and Physician Distress subscales and the lowest variability in the Powerlessness and Eating Distress subscales of the T1-DDS. Qualitative findings pointed out relevant concerns of people with T1D, which were not included in the T1-DDS. Conclusion: The study supports the use of the Danish T1-DDS, but also highlights that existing diabetes distress questionnaires including T1-DDS do not cover all potential diabetes stressors and worries.